Groundwater quality and its health impact: an assessment of dental fluorosis in rural inhabitants of the Main Ethiopian Rift - Rango, T.; Kravchenko, J.; Atlaw, B.; McCornick, Peter G.; Jeuland, M.; Merola, B.; Vengosh, A. (Elsevier, 2012)
This study aims to assess the link between fluoride content in groundwater and its impact on dental health in rural communities of the Ethiopian Rift. A total of 148 water samples were collected from two drainage basins within the Main Ethiopian Rift (MER). In the Ziway-Shala basin in particular, wells had high fluoride levels (mean: 9.4?10.5 mg/L; range: 1.1 to 68 mg/L), with 48 of 50 exceeding the WHO drinking water guideline limit of 1.5 mg/L. Total average daily intake of fluoride from drinking groundwater (calculated per weight unit) was also found to be six times higher than the No-Observed-Adverse-Effects-Level (NOAEL) value of 0.06 mg/kg/day. The highest fluoride levels were found in highly-alkaline (pH of 7 to 8.9) groundwater characterized by high salinity; high concentrations of sodium (Na+), bicarbonate (HCO3 -), and silica (SiO2); and low concentrations of calcium (Ca2+). A progressive Ca2+ decrease along the groundwater flow path is associated with an increase of fluoride in the groundwater. The groundwater quality problem is also coupled with the presence of other toxic elements, such as arsenic (As) and uranium (U). The health impact of fluoride was evaluated based on clinical examination of dental fluorosis (DF) among local residents using the Thylstrup and Fejerskov index (TFI). In total, 200 rural inhabitants between the ages of 7 and 40 years old using water from 12 wells of fluoride range of 7.8-18 mg/L were examined. Signs of DF (TF score of =1) were observed in all individuals. Most of the teeth (52%) recorded TF scores of 5 and 6, followed by TF scores of 3 and 4 (30%), and 8.4% had TF scores of 7 or higher. Sixty percent of the teeth exhibited loss of the outermost enamel. Within the range of fluoride contents, we did not find any correlation between fluoride content and DF. Finally, preliminary data suggest that milk intake has contributed to reducing the severity of DF. The study highlights the apparent positive role of milk on DF, and emphasizes the importance of nutrition in management efforts to mitigate DF in the MER and other parts of the world.